Legal Protection for Whistleblowers: A Review of Court Practices and Regulatory Gaps (Indonesian Court and Justice Review, 2024)
Whistleblowers play a critical role in exposing corruption, misconduct, and illegal activities within organizations, yet they often face significant personal and professional risks. In Indonesia, while legal frameworks exist to protect whistleblowers, challenges in enforcement, inconsistent judicial practices, and gaps in regulation hinder effective protection. This study reviews the current state of legal protection for whistleblowers in Indonesia, focusing on court practices, the application of whistleblower protection laws, and the regulatory gaps that expose individuals to retaliation. The research employs a qualitative approach, analyzing key case law, interviews with legal practitioners, and examining relevant statutory provisions to understand how courts address whistleblower cases. The findings reveal that, although Indonesia has made progress with laws such as the Anti-Corruption Law and the Whistleblower Protection Law, several barriers remain, including weak enforcement mechanisms, limited awareness among whistleblowers about their rights, and inconsistent rulings from the courts. This study highlights the urgent need for regulatory reform to enhance legal protections and strengthen the role of courts in safeguarding whistleblowers. The novelty of this research lies in its comprehensive review of both judicial practices and the broader regulatory environment, offering a holistic perspective on the challenges whistleblowers face in Indonesia. By contributing to the ongoing international dialogue on whistleblower protection, this study provides valuable insights for legal reforms aimed at ensuring a more robust and effective framework for whistleblowers in Indonesia.